2017
DOI: 10.1002/mus.25983
|View full text |Cite
|
Sign up to set email alerts
|

Low conversion rate of ocular to generalized myasthenia gravis in Singapore

Abstract: The conversion rate of OMG to GMG in Asian patients is low, as predicted by presence of acetylcholine receptor antibodies, presence of thymoma, and positive RNS studies. Muscle Nerve 57: 756-760, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
53
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 39 publications
13
53
2
Order By: Relevance
“…Contrast to 90% of conversion rate without immunosuppressive treatments, only 38 patients (17.0%) of 223 OMG patients under sufficient immunosuppressive treatments converted to GMG in the present study. This result was consistent with previous studies which compared the conversion rate of the immunosuppressed group and the non-immunosuppressed group [6,7,13,14]. Yet the predictors for these patients who received early immunosuppressive therapy still remain unknown.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Contrast to 90% of conversion rate without immunosuppressive treatments, only 38 patients (17.0%) of 223 OMG patients under sufficient immunosuppressive treatments converted to GMG in the present study. This result was consistent with previous studies which compared the conversion rate of the immunosuppressed group and the non-immunosuppressed group [6,7,13,14]. Yet the predictors for these patients who received early immunosuppressive therapy still remain unknown.…”
Section: Discussionsupporting
confidence: 92%
“…Whether positive RNS result could predict GMG conversion has not yet been completely elucidated. Previous reports indicated positive RNS could predict higher conversion rate [6,7]. Whereas other studies did not support this [1,4,6,22].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In Asia, the conversion rate was much lower due to the large proportion of juvenile-onset MG and the relative lower conversion rate (12.4-19.9%) [11,12]. Previous studies had revealed certain risk factors for OMG conversion, including older onset age, increased anti-ace-tylcholine receptor antibody (anti-AChR Ab) titer, presence of decrement on repetitive nerve stimulation (RNS), thymoma, and daily-life quality impairment due to the ocular symptoms [7,10,[13][14][15]. However, most studies recruited OMG patients with a wide age spectrum and did not filter out the potential confounding effect of immunosuppressing therapy.…”
Section: Introductionmentioning
confidence: 99%